2017
DOI: 10.1101/120170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding directional genetic dependencies through orthogonal CRISPR/Cas screens

Abstract: SummaryGenetic interaction studies are a powerful approach to identify functional interactions between genes. This approach can reveal networks of regulatory hubs and connect uncharacterised genes to well-studied pathways. However, this approach has previously been limited to simple gene inactivation studies. Here, we present an orthogonal CRISPR/Cas-mediated genetic interaction approach that allows the systematic activation of one gene while simultaneously knocking out a second gene in the same cell. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…However, in the context of mammalian metabolism the SKO CRISPR approach comes with limitations, as redundancies and plasticity of the metabolic network may allow the system to remodel around a SKO, thereby confounding analyses of impact on cellular fitness. To overcome this challenge, our group and others recently developed combinatorial gene knockout screening approaches which may provide a more suitable platform to study gene dispensability and also systematically map their interactions (Boettcher et al, 2017; Chow et al, 2017; Han et al, 2017; Shen et al, 2017; Wong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of mammalian metabolism the SKO CRISPR approach comes with limitations, as redundancies and plasticity of the metabolic network may allow the system to remodel around a SKO, thereby confounding analyses of impact on cellular fitness. To overcome this challenge, our group and others recently developed combinatorial gene knockout screening approaches which may provide a more suitable platform to study gene dispensability and also systematically map their interactions (Boettcher et al, 2017; Chow et al, 2017; Han et al, 2017; Shen et al, 2017; Wong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Single cell clones were verified by flow cytometry for a single high peak of BFP expression after 3-4 wk of growth. Sequences against Endo180 or a nontargeting control (Table 1) were cloned into a pSicoR-puro-mCherry backbone under a U6 promoter for singleguide RNA (sgRNA) synthesis, which was a gift from Michael McManus (6). Plasmids were synthesized into lentiviral particles by University of California, San Francisco ViraCore.…”
Section: Methodsmentioning
confidence: 99%
“…Our strategy first identified high-confidence hit genes using an ultracomplex shRNA library for a specific phenotype following which we generated double-shRNA libraries to construct a GI map between the gene-pairs. More recently, similar approaches have been implemented based on CRISPR technology, including CRISPR-cutting (1720), CRISPRi (21,22) and CRISPRa (23). We recently demonstrated that combined gain-and-loss of function GI maps leveraging orthogonal CRISPR cutting and CRISPRa approaches can enable the elucidation of directional pathway information (23).…”
Section: Systematic Large-scale Gi Mapsmentioning
confidence: 99%